Формализация описания компьютерных приложений на основе графических нотаций - Бальва, А.А.; Самойлов, В.Д. (Электронное моделирование, 2011)
Обоснована целесообразность создания графических моделей компьютерных приложений на всех этапах их жизненного цикла. Для их описания выбраны графические нотации стандарта IDEF. Определены правила построения графических моделей систем данного класса. В качестве примера приведена графическая модель системы обучения и контроля знаний. Обґрунтовано доцільність створення графічних моделей комп’ютерних додатків на всіх етапах їхнього життєвого циклу. Для їхнього опису обрано графічні нотації стандарту IDEF. Визначено правила побудови графічних моделей систем даного класу. Як приклад наведено графічну модель системи навчання і контролю знань. The necessity of creating of graphical models for computer applications at all stages of their life cycle has been substantiated. Based on the analysis of technologies and means of visual system design, using typical features of computerized systems of expert training and competence test and available in the market at this stage, IDEF standard graphical notations have been selected for its description. The rules for construction of graphical models for systems of such class have been elaborated. A graphical model of the KONKURS system is presented as an example.